Learners Acceptance of u-KIT EDU as an Educational Application for Robot Building, Coding, and Controlling - Virgiawan Listanto; Arif Ramadhan; Nurhuda Firmansyah; Baiq Hana Susanti (Universitas Pendidikan Ganesha, 2023)
Humans tend to always look for convenience, including choosing applications to learn robot programming. uKIT EDU is an educational application for robot building, coding and controlling. This study aims to analyze new learners' level of acceptance towards it. This research was designed quantitatively by involving 116 respondents. A questionnaire based on the Technology Acceptance Model (TAM) was organized with 4 observed variables, including perceived usefulness, perceived ease of use, attitude and behavioral intention to use. The Mann-Whitney U statistical test was carried out in this study to compare two independent samples, male and female learners. Moreover, the Kruskal-Wallis H statistical test was carried out to compare three or more independent samples based on age generations and occupations. From all the statistical tests conducted, it was found that there was no significant difference in the acceptance of uKIT EDU from each sample based on gender, age generations and occupation. They agreed that the app was useful and easy to be used to learn robotics, coding and controlling. Briefly, this study revealed that uKIT EDU is suitable for new learners and can be used as a reference for any schools, educational institutions, and parents of students interested in starting to learn robotics.